The Influence Of Product Quality, Service Quality, And O2O Digital Marketing On The Purchase Decision Of Make Over Cosmetic Products - Lhia Flora Triwinarti Tambunan; Annisa Sanny; Annisa Febrina (International Journal of Management, Economic and Accounting, 2025)
This study aims to analyze product quality, service quality and digital marketing online to offline on the purchase decision of make over cosmetic products. Where there is a bound variable, namely the purchase decision and there are three independent variables: product quality, service quality and digital marketing. This study uses primary data by searching for data through the Make Over Transmart Plaza Medan Fair store. The data analysis model in this study uses multiple linear regression. The results of the study showed that the variables of product quality, service quality and digital marketing had a significant effect on consumer purchase decisions at the Make Over Transmart Plaza Medan Fair store.